Local Economic Interactions in Border Areas (Study of Local Community Economy on the Sota-Papua New Guinea Border) - Mite, Elias; Ngarawula, Bonaventura; ., Sukardi; ., Fitriani (Journal of Ecohumanism, 2025)
This study aims to analyze the driving and inhibiting factors of local economic interaction in the border area of ​​Sota (Indonesia) and Papua New Guinea (PNG). The focus of the study is directed at identifying internal and external factors that influence the economic activities of local communities on the border. The study uses a descriptive qualitative approach through field observations, in-depth interviews with local communities, traders, and government officials, and secondary data documentation. The results of the study indicate that local economic interaction on the Sota-PNG border is driven by several internal factors, namely the mutual needs of the community for basic necessities, social relations and kinship across countries, and the community's ability to adapt in exchanging goods. From the external side, the availability of traditional border markets, significant differences in the price of goods between Indonesia and PNG, and the existence of traditional cross-border permits are the main drivers. However, this economic interaction also faces various obstacles. Internal inhibiting factors include limited business capital, minimal local economic infrastructure, and dependence on supplies from outside the region. Meanwhile, from external factors, the main obstacles include regional restrictions by security forces, geographic conditions and extreme weather that complicate transportation, fluctuations in currency exchange rates, and limited border infrastructure. The conclusion of this study confirms that local economic interaction in the Sota-PNG border area has an important role in meeting the needs of the community, although it still faces various challenges that require attention from the governments of both countries.